(untitled) (LIS TODAY, 2023)
The library field is passing in re-innovation age, some latest technological developments have been found to be very effective in providing library services in innovative way and made library automation services more effective and cost saving also. Latest technologies like QR code technology, RFID technology, Cloud computing technology, Robotics etc are some of them. The present paper focuses on cloud computing and its role in enhancement of library services. It describes how cloud computing may be useful in providing library services and making it cost effective as well.